Interaction Between Heart Rate Variability and Heart Rate in Pediatric Population - Gąsior, Jakub S.; Sacha, Jerzy; Jeleń, Piotr J.; Pawłowski, Mariusz; Werner, Bożena; Dąbrowski, Marek J. (Frontiers in Physiology, 2015)
Background: Heart rate variability (HRV) is primarily heart rate (HR) dependent, and therefore, different HR may exert different impact on HRV. The objectives of the study were to evaluate the effect of HR on HRV in children and to determine whether HRV indices normalized to HR are sex- and age-related. Methods: Short-term ECG recordings were performed in 346 healthy children. Standard time and frequency domain HRV parameters and HR were analysed in four age subgroups (6-7, 8-9, 10-11 and 12-13 years old). To investigate the HR impact on HRV, standard HRV parameters were normalized to prevailing HR. Results: Standard HRV measures did not differ between age subgroups, however, HR significantly decreased with subjects age and turned out to be the strongest determinant of HRV. The normalization of HRV to prevailing HR allowed to show that sex-related differences in standard HRV resulted from differences in HR between boys and girls. The normalized HRV significantly decreased with age – before the normalization this effect was masked by age-related HR alterations. Conclusions: HR significantly impacts HRV in pediatric population and turns out to be the strongest determinant of all standard HRV indices. The differences in standard HRV between boys and girls result from differences in their HR. The normalized HRV is decreasing with age in healthy children and it is accompanied by the reduction of HR – as a net result, the standard HRV is constant in children at different ages. This may reflect the maturation of the autonomic nervous system.